Understanding Abstract Concepts across Modes in Multimodal Discourse A Cognitive Linguistic Approach. Elżbieta Górska. - Elena Mattei (Iperstoria, 2020)
Review of Understanding Abstract Concepts across Modes in Multimodal Discourse. A Cognitive Linguistic Approach, by Elżbieta Górska.